Redescription and phylogenetic placement of the Hispaniolan spider genus Lomaita Bryant, 1948 (Araneae, Linyphiidae) - Da Silva-Moreira, Thiago; Hormiga, Gustavo (Zootaxa, 2015)
The monotypic linyphiid genus Lomaita Bryant 1948 is redescribed. We present an updated description of the male of L. darlingtoni, the first description of the female and data on its natural history and distribution in the Dominican Republic. We provide a hypothesis on the phylogenetic placement of Lomaita based on cladistic analyses of morphological characters.